Failure mechanisms of calcium magnesium aluminum silicate affected thermal barrier coatings. Issue 6 (20th March 2017) - Thornton, John; Wood, Chris; Kimpton, Justin A.; Sesso, Mitchell; Zonneveldt, Matthew; Armstrong, Nicholas
Abstract: Depth profiles of the phase composition of two examples of calcium magnesium aluminum silicate (CMAS) affected thermal barrier coatings (TBCs) from an aero gas turbine engine were obtained using a monochromatic and collimated beam of synchrotron radiation. One TBC was deposited by plasma spray and the other by electron beam physical vapor deposition. These examples were complemented with an X‐ray diffraction (XRD) study of mixtures of TBC zirconia powder and sand heated in a furnace. The XRD results were compared with electron backscatter images and energy dispersive spectroscopy studies of the cross sections and mixtures. It was found that when liquid, the CMAS enhances mass transport leading to the densification of the zirconia, which then leads to spalling because of the increased residual stresses generated on cooling. Even without spalling densification will reduce a TBC's ability to thermally insulate. The enhanced mass transport can also lead to destabilization of the zirconia if yttrium ions preferentially transfer to the liquid or greater stabilization if calcium or magnesium ions transfer from the liquid to the zirconia. Zircon also precipitates when the zirconium from the TBC reacts with the silicon in the liquid CMAS.